2021
DOI: 10.26803/ijlter.20.4.5
|View full text |Cite
|
Sign up to set email alerts
|

What do College Learners Think of Synchronous Learning?

Abstract: Advancements in educational technology and improvements in the internet’s connectivity has increased the interest of universities in e-learning worldwide. Unlike many institutions around the world, the traditional form of teaching in Albania before the Covid-19 pandemic was face-to-face where both lectures and seminars were attended physically in the classroom. However, the Covid-19 pandemic imposed on them the necessity to move from auditoriums to e-learning immediately without any preparation. This paper aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…[82] Teachers stated that they felt uncomfortable with technical and psychological factors. [83] Readiness and experience are important factors [84] Opportunity to collaborate, discuss and think about their professional development [85] Lack of social interaction [86] "time efficiency" and "lack of interaction" [87] Confidence, Saving effort, money, and time, quick feedback [88] The lack of motivation, low level of interaction [89] New teaching approaches with online learning [90] Teaching methods, social aspects, infrastructure, computer skills, assessment methods, motivation, and willingness [91] Students have difficulties in their self-learning activities. They still prefer direct lessons to understand the materials during e-learning.…”
Section: Descriptive Analysis Of Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…[82] Teachers stated that they felt uncomfortable with technical and psychological factors. [83] Readiness and experience are important factors [84] Opportunity to collaborate, discuss and think about their professional development [85] Lack of social interaction [86] "time efficiency" and "lack of interaction" [87] Confidence, Saving effort, money, and time, quick feedback [88] The lack of motivation, low level of interaction [89] New teaching approaches with online learning [90] Teaching methods, social aspects, infrastructure, computer skills, assessment methods, motivation, and willingness [91] Students have difficulties in their self-learning activities. They still prefer direct lessons to understand the materials during e-learning.…”
Section: Descriptive Analysis Of Articlesmentioning
confidence: 99%
“…[106] The biggest challenge is facing the network connection and electricity in South Africa. [87] Many elements that helped academics adopt e-assessments were identified as usefulness, exam preparation, cost, ease of use, and increase satisfaction. [107] It has been shown that the use of e-learning systems plays a leading role in increasing students' intention to participate in e-learning.…”
Section: Descriptive Analysis Of Articlesmentioning
confidence: 99%
“…Different parts of the world and specific scholastic contexts have different challenges to address in order to maximize the effectiveness of their school systems. The studies reviewed in the previous section (Beka 2021, Taraj 2021, Aduba & Mayowa-Adebara 2021, Lagumdžija & Eminović-Ljevo 2021, Venable 2021, Barron Rodriguez et al 2020) reveal that experiences with online education vary. All of them report various challenges that need to be addressed, such as internet infrastructure, lack of electronic devices, underexplored potentials of digital education, the power of social and interactive contact, or a lack of collective awareness about pitfalls of digital education.…”
Section: Relying On Optimism Is Not Enoughmentioning
confidence: 99%